2015
DOI: 10.5007/2175-7968.2015v35nesp2p458
|View full text |Cite
|
Sign up to set email alerts
|

Tradução de libras para português de textos acadêmicos: considerações sobre a prática

Abstract: Resumo: Este artigo objetiva apresentar ao leitor algumas considerações acerca do trabalho de tradução de textos acadêmicos produzidos em Lín-gua Brasileira de Sinais (Libras) para o Português em sua modalidade escrita. O trabalho possui como recorte a tradução de uma tese de doutorado produzida em Libras e registrada em vídeo por uma acadêmica surda da Universidade Federal de Santa Catarina, UFSC. As considerações são aqui apresentadas seguindo os fatores extratextuais e intratextuais de Nord (1991) propostos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Additionally, regarding intermodal translation, we have observed that there are some specificities related to its operationalization, since signed languages recorded on video are commonly employed as the final product of the translation of written or oral texts produced in spoken languages. Moreover, the translation of sign languages has been increasing significantly nowadays, especially within the academic environment, with its different directions and possibilities (Wurm 2010, Rodrigues, Beer 2015, Rigo 2015.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Additionally, regarding intermodal translation, we have observed that there are some specificities related to its operationalization, since signed languages recorded on video are commonly employed as the final product of the translation of written or oral texts produced in spoken languages. Moreover, the translation of sign languages has been increasing significantly nowadays, especially within the academic environment, with its different directions and possibilities (Wurm 2010, Rodrigues, Beer 2015, Rigo 2015.…”
Section: Final Considerationsmentioning
confidence: 99%